Resolving Barriers to Licensure Portability for Telerehabilitation Professionals - Ellen R. Cohn; Janice A. Brannon; Jana Cason (International Journal of Telerehabilitation)
Rehabilitation professionals (e.g., audiologists, occupational therapists, physical therapists, speech-language pathologists, etc.) can only engage in telerehabilitation in states in which they hold a professional license. The current state-based licensure and regulation of rehabilitation professionals does not facilitate the practice of telerehabilitation across state lines. Given today’s equipment capabilities and consumer adoption of the electronic delivery of many kinds of services, health care providers, including rehabilitation professionals, should be able to serve clients wherever they are needed.